Memahami Isrâ’îliyyât dalam Penafsiran Al-Qur’an - Usman Usman (Ulumuna, 2011)
Isrâ’îliyyât, mostly, known as non-muslim based narration, particularly Jewish, which is later inserted into Islamic tradition and thoughts. Some mufassirs utilize this narration as a method of interpeting Qur’an and it unavoidably arises controversy between the classic muslim scholars and the modern one. However, the dispute between both groups should be carefully discussed and wisely selected. In doing so, their debate could contribute some positive and negative points for Islam and muslim developments.